Anarchist Pedagogy in the Gender and Women’s Studies Classroom - Soderling, Stina (Atlantis)

(untitled) (Mount Saint Vincent University, 2016)
This article argues for the value of employing anarchist pedagogical methods in introductory Gender and Women’s Studies courses. The author draws on her experiences using feminist and anarchist pedagogical literature as well as her own experiences using anarchist pedagogy. Topics addressed include classroom structure, syllabus design, grading, and the question of opinions and neutrality.